2011
DOI: 10.4172/2155-9899.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Cytokines and Atopic Dermatitis

Abstract: Atopic dermatitis (AD), a chronic relapsing inflammatory skin disease, is increasing in prevalence around the world. Intensive research is ongoing to understand the mechanisms involved in the development of AD and offer new treatment options for patients suffering from AD. In this review, we highlight the importance of allergic Th2 responses in the development of the disease and summarize relevant literature, including genetic studies, studies of human skin and mechanistic studies on keratinocytes and mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
459
1
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(480 citation statements)
references
References 172 publications
(211 reference statements)
9
459
1
11
Order By: Relevance
“…Several previous studies (1, 37, 38) have shown that human IL-31RA is expressed on monocytes/macrophages, keratinocytes, epithelial cells, and dendritic cells. In addition, increased IL-31 and IL-31RA levels have been found in Th2-related allergic diseases, such as atopic dermatitis (39), which is characterized by the polarization of antigen-presenting cells and activation of a Th2 response (40). In a mouse model of atopic dermatitis, increased IL-31 transcripts were associated with scratching behavior (41), whereas a recent study showed that anti-IL-31 neutralizing antibody reduces scratching behavior and dermatitis in mice (12).…”
Section: Sea-challenged Il-13r␣1mentioning
confidence: 99%
“…Several previous studies (1, 37, 38) have shown that human IL-31RA is expressed on monocytes/macrophages, keratinocytes, epithelial cells, and dendritic cells. In addition, increased IL-31 and IL-31RA levels have been found in Th2-related allergic diseases, such as atopic dermatitis (39), which is characterized by the polarization of antigen-presenting cells and activation of a Th2 response (40). In a mouse model of atopic dermatitis, increased IL-31 transcripts were associated with scratching behavior (41), whereas a recent study showed that anti-IL-31 neutralizing antibody reduces scratching behavior and dermatitis in mice (12).…”
Section: Sea-challenged Il-13r␣1mentioning
confidence: 99%
“…4A), suggesting that LX519290 inhibited cytokine production or decreased the levels of skin T cells and mast cells. Since there has been many convincing results as molecular inflammation and allergic diseases of cytokines such as IL-4, IL-13, IL-31, IL-33, and IL-35, 26) the present data suggest that LX519290 has anti-atopic activities on mouse skin tissues by decreasing IL-17E and histamine levels.…”
Section: Resultsmentioning
confidence: 65%
“…As a result, and despite the occurrence of late-onset AD in some adults, the prevalence of AD in the adult population has been estimated to be much lower (2-9%) [14][15][16]. Multiple factors are involved in the pathogenesis of AE including genetic predisposition, impaired skin barrier function, microbial colonization and sensitization against environmental allergens.…”
Section: Atopic Dermatitismentioning
confidence: 99%